带传动的动态分析及寿命的评估 - 闻欣荣; 孔建益 (Jixie chuandong)
The nonage fracture of belt is a difficult problem in belt drive. No doubt, the research on the vibrations of belt-drums system would certainly be of advantage for reduction of this difficulty. So that, in this paper the vibrations of belt-drums system are analyzed. the presented solutions can be directly applied to determine the tensile forces of belt. Using the obtained solutions together with the fatigue equation by experiments, the tensile forces and cause of nonage fracture for belt are discussed. The results show that the tensile forces under static conditions are small cmpared with those in actual states, and also that the belt life, due to increase of dynamic stress, may be several times smaller than that in static. Thus, the belt life obtained under static conditions is not reliable. Furthermore, in order to check the reliability of differential equations established and its solutions obtained in this paper, an example is worked out in detail. It is shown that if the dynamical terms in solutions obtained are neglected, the results specialized to the static case not only show a close agreement with the classical formulas, but the results of numeral calculations are obviously identical with those in literature. So that, the result in this paper lades to a theoretical modification to a classical method and it is also a method to enhance the precision of life prediction for belt.